2012
DOI: 10.1017/s0960428611000382
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Soils on the Floristic Composition and Community Structure of an Area of Brazilian Cerrado Vegetation

Abstract: This study investigated the influence of soil factors on the structure, richness and distribution of woody Cerrado species within the National Forest of Paraopeba, Minas Gerais State, Brazil. Individuals with basal stem circumference $ 10 cm were sampled in five plots of 20 3 100 m. The study was conducted in five environments with different physiognomies and types of soils. A total of 132 species were recorded. The species with the greatest importance values varied between different areas, as did structure. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
2
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 19 publications
4
36
2
15
Order By: Relevance
“…The occurrence of Astronium fraxinifolium and Terminalia argentea, which have a weak preference for mesotrophic soils, is not surprising; however, the other species are certainly unexpected. These anomalies have been recorded in other studies (Ratter, personal communication;Araújo et al 2011;Neri et al 2012), and it has been suggested that they occur on mesotrophic soils within dystrophic landscapes.…”
Section: Floristics and Structuresupporting
confidence: 75%
“…The occurrence of Astronium fraxinifolium and Terminalia argentea, which have a weak preference for mesotrophic soils, is not surprising; however, the other species are certainly unexpected. These anomalies have been recorded in other studies (Ratter, personal communication;Araújo et al 2011;Neri et al 2012), and it has been suggested that they occur on mesotrophic soils within dystrophic landscapes.…”
Section: Floristics and Structuresupporting
confidence: 75%
“…Neri et al (2012) encontraram correlações positivas entre áreas de elevada área basal e teores de fósforo. Portanto, acredita-se que o que melhor explica e sustenta uma comunidade arbórea de cerrado rupestre sobre neossolos litólicos seja o elevado teor de minerais primários disponíveis.…”
Section: Discussionunclassified
“…The Cerrado covers around 204 million hectares of Central and part of Northern Brazil (IBGE 2013). Due to rainfall seasonality, soil fertility, drainage properties and the occurrence of fire, the Cerrado structure ranges from the treeless Bcampo^to a relatively dense forest of trees of approximately 15 m in height (Neri et al 2012). Indeed, its biodiversity is very high, including the existence of endemic species.…”
Section: Challengesmentioning
confidence: 99%